THE EFFECT OF BIOSTIMULATORS ON THE BIOLOGICAL DEVELOPMENT OF KORAKUL SHEEP - Sh. A. Chalaboyev; Kh. Yunusov; N. Farmonov; G. Kuldoshev (Web of Journals Publishing, 2024)
In this article, in order to determine the pharmacostimulating effect of various pharmacological drugs (Butasal, Miosta-H, E-selenium) on the animal body, an increase in their body weight, growth and development was carried out on Karakul lambs. The effect on body temperature, respiration rate per minute and heart rate.
Keywords: Butasal, Miosta-H, Ye-selenium, frequency, pharmacostimu-lation, regenerative, biopreparation, electronic scale.